THE VALUE OF LOCAL WISDOM IN JEPARA’S LOMBAN TRADITION - Dewi Puspita Ningsih (Jurnal Ilmiah Mandala Education (JIME), 2017)
This study aims to investigate how  the tradition of lomban is conducted and what are  the values containing in Jeparas people belief. This was a qualitative descriptive study with culture sociology approach. This study is conducted within two weeks. The subject of research is  religious leader, culture figures, stakeholder and informan in community surrounding. The informants were selected by means of the snowball sampling technique. The data collection techniques included an observation, an interview, and documentation. The analyzed through the steps of: 1) data reduction, 2) data abstraction, and 3) conclusion drawing. The research findings are as follows that lomban tradition is conducted in a week after idul fitri celebration, the tradition is as gratefull expression to the lord of north sea and asking for safety and prosperity to the god. The value of local wisdom in lomban tradition give good impact in social, economy,culture and religion field